Overview of breast cancer collaborative stage data items—their definitions, quality, usage, and clinical implications: A review of SEER data for 2004‐2010. (1st December 2014) - Howlader, Nadia; Chen, Vivien W.; Ries, Lynn A. G.; Loch, Michelle M.; Lee, Richard; DeSantis, Carol; Lin, Chun Chieh; Ruhl, Jennifer; Cronin, Kathleen A.
Abstract : BACKGROUND: Surveillance, Epidemiology, and End Results (SEER) Program registries began collecting new data items, known as site‐specific factors (SSFs), related to breast cancer treatment, prediction, and prognosis under the Collaborative Stage version 2 (CSv2) Data Collection System for cases diagnosed in 2010. The objectives of this report are to: 1) assess the completeness of the new SSFs and discuss their limitations and 2) discuss key changes in American Joint Committee on Cancer (AJCC) staging between the 6th and 7th editions. METHODS: We used data from the 18 SEER population‐based registries (SEER‐18), which included 71, 983 women diagnosed with breast cancer in 2010. RESULTS: Of the 18 SSFs examined in this study, 6 SSFs were more than 75% complete. Information on estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2), was available for more than 90% of the invasive breast cancer cases. These data are required to categorize the distinct subtypes of breast cancer. The majority of cases also had information on other prognostic factors such as Bloom‐Richardson score/grade (83%) and the size of invasive component in the tumor (76%). As a result of changes in staging criteria, nearly 10% of cases categorized as stage IIA according to the 6th edition of the AJCC staging manual were downstaged to stage IB under the 7th edition. CONCLUSIONS: The Collaborative Stage data collection system enables registries to collect current, relevant, and standardized data items that are consistent with the evolving view of breast cancer as a heterogeneous disease. Cancer 2014;120(23 suppl):3771‐80. © 2014 American Cancer Society . Abstract : This report discusses the utility and limitations of the new breast cancer variables to be collected under the Collaborative Stage Data Collection System for researchers who intend to analyze these variables using population‐based SEER or other North American cancer registry data. The report also highlights differences between the American Joint Committee on Cancer's (AJCC) 6th and 7th editions for classifying breast cancer stage.